Human computer interaction development and management - Barrier, Tonya, 1959- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2002)
Organizations cannot continue to blindly accept and introduce components into Information Systems without studying the effectiveness, feasibility and efficiency of the individual components of their information systems. Information Systems may be the only business area where it is automatically assumed that the "latest, greatest and most powerful component is the one for our organization" and must be managed and developed as any other resource in organizations today. This book contains the most recent research articles concerning the management and development of Information Systems, so that organizations can effectively manage information systems growth and development. Not only must hardware, software, data, information, and networks be managed--people must be managed. Humans must be trained to use information systems. Systems must be developed so humans can use the systems as efficiently and effectively as possible.